An impact of treatment initiation timing on stroke outcome: bridging the time gap - Kuanysh Nikatov; Ermek Dyussembekov; Rauan Kastey; Yevgeniy Zhukov; Niyazbek Yerniyazov; Mukhtar Korabayev; Gani Akhanov; Timur Saliev; Ildar Fakhradiyev (Medicinski glasnik, 2023)
Aim: Stroke treatment is a time-critical condition. Understanding the impact of timing and types of treatment on patient outcomes can help develop and optimize stroke management strategies. The study aimed to analyse the effect of different time intervals and mechanical thrombectomy methods on outcomes of stroke patients in Kazakhstan. Methods: The patient data, including demographic information, clinical characteristics, and specific time intervals from stroke onset to hospital admission, stroke onset to surgery initiation, and hospital admission to surgery initiation were collected. A total of 100 patients were analysed. Patients’ neurological status was evaluated using the National Institutes of Health Stroke Scale (NIHSS), Modified Rankin Scale (mRS), and Glasgow Coma Scale (GCS) before and after the surgical treatment. Results: Most patients had concomitant arterial hypertension, and almost 25 % had diabetes mellitus. The average time from stroke onset to hospital admission was 123.2±7.6 minutes, and from hospital admission to surgery initiation, it was 134.7±13.1 minutes. A shorter duration from the onset of stroke to hospitalization and surgery was associated with better clinical outcomes. Our results demonstrated a statistically significant decrease in NIHSS, mRS after surgical treatment compared to baseline. The association between the extended time from stroke onset to hospitalization and reduced survival rates was observed. Conclusion: Our findings indicate the essential role of timely intervention in managing stroke patients, as well as the need for a comprehensive and patient-centred approach to stroke care.
Keywords: cerebrovascular accident; hospitalization; mechanical thrombolysis; treatment delays